2001
DOI: 10.1016/s0896-6273(01)00293-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ablation of Orexin Neurons in Mice Results in Narcolepsy, Hypophagia, and Obesity

Abstract: Orexins (hypocretins) are a pair of neuropeptides implicated in energy homeostasis and arousal. Recent reports suggest that loss of orexin-containing neurons occurs in human patients with narcolepsy. We generated transgenic mice in which orexin-containing neurons are ablated by orexinergic-specific expression of a truncated Machado-Joseph disease gene product (ataxin-3) with an expanded polyglutamine stretch. These mice showed a phenotype strikingly similar to human narcolepsy, including behavioral arrests, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

48
1,044
5
11

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,305 publications
(1,108 citation statements)
references
References 32 publications
48
1,044
5
11
Order By: Relevance
“…First, rather than only stimulating food intake, downstream effects of hypocretins on energy consumption might be more important to the regulation of body homeostasis. In fact, hypocretin knockout mice have normal body weight and ataxin-3 mutants with absent hypocretin containing-cells have increased body weight (Hara et al 2001), an effect inconsistent with a decreased orexinogenic signal. Obesity is generally believed to reflect decreased metabolic activity and energy expenditure in hypocretin deficient animals, an effect that would be quantitatively more important than hypophagia.…”
Section: Food Intake Energy Metabolism and Neurohormonal Control Of mentioning
confidence: 99%
“…First, rather than only stimulating food intake, downstream effects of hypocretins on energy consumption might be more important to the regulation of body homeostasis. In fact, hypocretin knockout mice have normal body weight and ataxin-3 mutants with absent hypocretin containing-cells have increased body weight (Hara et al 2001), an effect inconsistent with a decreased orexinogenic signal. Obesity is generally believed to reflect decreased metabolic activity and energy expenditure in hypocretin deficient animals, an effect that would be quantitatively more important than hypophagia.…”
Section: Food Intake Energy Metabolism and Neurohormonal Control Of mentioning
confidence: 99%
“…In humans, narcolepsy is accompanied by energy imbalance, such as decreased energy intake and increased BMI, resulting in an increase in the incidence of type 2 diabetes [12][13][14][15]. Mice deficient in orexin neurons also exhibit late-onset obesity, despite eating less [16], and on a high-fat diet, become heavier than wildtype mice [17]. Thus, orexin neurons appear to provide a crucial link between arousal and energy balance [1,11,18].…”
mentioning
confidence: 99%
“…An important difference in the effects on feeding between orexin and other orexigenic factors, such as NPY and melanin-concentrating hormone (MCH), is that orexin increases both food intake and energy expenditure MM&TS 10 (Lubkin and Stricker-Krongrad, 1998;Hara et al, 2001), while other feeding peptides generally decrease energy expenditure (Spiegelman and Flier, 2001): the latter response is more adaptive to conserving energy under food scarcity. Increased energy expenditure by orexin administration seems to be caused by increased wakefulness and locomotor activity, as well as an increase in sympathetic outflow.…”
Section: Integrative Physiology Of Orexin Systemmentioning
confidence: 99%
“…Indeed, orexin deficiency decreases sympathetic tone (Kayaba et al, 2003;Zhang et al, 2006), resulting in reduced energy expenditure. This may explain why human and mouse narcolepsy are associated with an increase of body weight despite hypophagia (Lammers et al, 1996;Schuld et al, 2000;Hara et al, 2001). Additionally, a recent work suggested that orexin enhances leptin-sensitivity through an OX2R-mediated mechanism (Funato et al, 2009).…”
Section: Integrative Physiology Of Orexin Systemmentioning
confidence: 99%